Putusan Mk Nomor 39/PUU-XVII/2019 sebagai Dasar Hukum untuk Menentukan dan Menetapkan Pemenang Pemilu Presiden - Prabaswara, Fernindito Radiktya; Husodo, Jadmiko Anom (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2021)
ABSTRACTThis study aims to determine whether the Constitutional Court Decision Number 39 / PUU-XVII / 2019 can be used as a legal basis for determining and assigning the winner of a presidential election. This research is a prescriptive normative legal research. The research approach that I use is a statutory approach with data sources obtained through primary and secondary data. Primary data were obtained from laws and rulings, while secondary data were obtained through literature studies, namely books, journals and scientific articles, legal dictionaries and materials from internet media. The data collection technique used is literature study, so that the writing of this law is then understood as writing literature, namely research on secondary data. Based on the results of this study, the authors conclude that theConstitutional Court’s decision does not yet have strong force to become the legal basis for determining the winners of the presidential and vice presidential electionsand even though the principles of justice and truth have been reached, there is no guarantee that the decision will be obeyed.Keywords: legal basis; judicial judgment; general election.